A Study on the Production Method of Kenaf High Fiber Strength - Wiwin Suwinarti; Zhou Chen; Susumu Nakahara; Ryo Sugawara; Kazuhiko Sameshima (Wood Research Journal, 2011)
Kenaf bast fiber from 58 varieties grown in Zhejiang province, China, was treated using three treatments. First treatment used ammonium oxalate, sodium hydroxide and acidic chlorite (AT3), second treatment used ammonium oxalate and sodium hydroxide (AT0) and the third one was retting treatment (RET). Some parameters such as diameter, height and weight of stalk, and also fiber strength were measured for screening method.Treatment AT3 show much better strength than the other two. It means the single fiber which belongs to AT3 is stronger than the bundle fiber of AT0 and RET. Moreover the chemical treatment of AT0 has much stronger bundle fiber than RET. The best-8 varieties (kenaf sample number 8, 11, 12, 30, 32, 48, 52 and 58) were selected based on the fiber strength and kenaf sample number 12 and 32 reached the superior two if evaluated with other factors.